2000
DOI: 10.1042/cs0980217
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone receptor expression and action in bone

Abstract: The skeleton is a complex tissue, and hormonal control of bone remodelling is elaborate. The important role that steroid hormones play in bone cell development and in the maintenance of normal bone architecture is well established, but it is only relatively recently that it has become possible to describe their precise mechanism of action. This review focuses not only on the steroid hormones (oestrogens, corticosteroids, androgens and progesterone), but also on related hormones (vitamin D, thyroid hormone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1
13

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 204 publications
(267 reference statements)
1
67
1
13
Order By: Relevance
“…Localization studies indicate that ER and Rho GDI are found in distinct subcellular compartments, with Rho GDI residing in the cytoplasm, whereas ER is confined to the nucleus. 3 In addition, GST-Rho GDI is unable to associate with estradiol-bound ER, although it is capable of binding Rho A in vitro. 3 While Brx and Rho GTPases may modulate ER activity through distinct mechanisms, the identification of different components in the Rho signaling pathway as modulators of ER transactivation underscores their importance in receptor regulation.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Localization studies indicate that ER and Rho GDI are found in distinct subcellular compartments, with Rho GDI residing in the cytoplasm, whereas ER is confined to the nucleus. 3 In addition, GST-Rho GDI is unable to associate with estradiol-bound ER, although it is capable of binding Rho A in vitro. 3 While Brx and Rho GTPases may modulate ER activity through distinct mechanisms, the identification of different components in the Rho signaling pathway as modulators of ER transactivation underscores their importance in receptor regulation.…”
Section: Figmentioning
confidence: 99%
“…Although the mechanism of this increased ER transcriptional activation remains to be elucidated, it probably involves phosphorylation-dependent cofactor recruitment (68). Thus, Ras acts as a positive regulator of ER transcriptional enhancement (67), 3 whereas Rho GTPases suppress receptor transactivation. We speculate that the opposing actions of Ras and Rho GTPases on ER-mediated transcriptional activation provide a means of fine tuning the ER transcriptional response to changes in the extracellular environment.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…teroid sex hormones are essential for normal skeletal development and maintenance of healthy bone remodeling during adult life (1,2). Sex hormone status reflects bone mass, such that hormonal deficiency is well known to lead to progressive bone loss (3).…”
mentioning
confidence: 99%
“…ERa and ERb are each expressed in osteoblasts and osteoclasts (Lim et al, 1999;Bland, 2000;Bord et al, 2001). The potential roles of the 2 ER isoforms in bone homeostasis are under intense investigation.…”
Section: Introductionmentioning
confidence: 99%